2006
DOI: 10.1038/sj.bjc.6603048
|View full text |Cite
|
Sign up to set email alerts
|

Side effects associated with the use of dexamethasone for prophylaxis of delayed emesis after moderately emetogenic chemotherapy

Abstract: The role of dexamethasone to reduce delayed emesis following highly emetogenic chemotherapy is proven, but there is less evidence of benefit after mild -moderately emetogenic regimens. Here, we develop and evaluate a Dexamethasone Symptom Questionnaire (DSQ) to assess the side effects of dexamethasone in the week after patients receive moderately emetogenic chemotherapy. The DSQ was first optimised with the aid of a focus group. Sixty patients receiving oral dexamethasone for prophylaxis of delayed emesis afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(104 citation statements)
references
References 31 publications
1
101
1
1
Order By: Relevance
“…In a study by Vardy et al [22], patients receiving DEX for prevention of delayed CINV reported the following adverse events in the week following chemotherapy: moderate-to-severe insomnia (45%), indigestion and/or epigastric discomfort (27%), agitation (27%), increased appetite (19%), weight gain (16%) and acne (15%). As a result, there has been interest in minimizing the DEX dose and frequency, especially in patients who experience these DEX-related side effects.…”
Section: Antiemeticsmentioning
confidence: 99%
“…In a study by Vardy et al [22], patients receiving DEX for prevention of delayed CINV reported the following adverse events in the week following chemotherapy: moderate-to-severe insomnia (45%), indigestion and/or epigastric discomfort (27%), agitation (27%), increased appetite (19%), weight gain (16%) and acne (15%). As a result, there has been interest in minimizing the DEX dose and frequency, especially in patients who experience these DEX-related side effects.…”
Section: Antiemeticsmentioning
confidence: 99%
“…[1113] Weight gain during treatment is thought to be in-part due to increased appetite from the corticosteroids used for chemotherapy-induced nausea and vomiting prophylaxis, while long-term weight increases in some instances may be due to chemotherapy-related hormonal changes. [14,15]…”
Section: Introductionmentioning
confidence: 99%
“…However, we believe our results do demonstrate the utility of PALO in the delayed setting, as no corticosteroids were used. While the use of corticosteroids in the delayed setting has been shown to decrease the risk of nausea from chemotherapy, they have also been shown, even when used for short durations, to result in intolerable side effects such as insomnia, indigestion/epigastric discomfort, agitation and acne in the week following chemotherapy [9,11,17]. With the addition of PALO, we were able to improve control of CINV without the use of dexamethasone.…”
Section: Discussionmentioning
confidence: 97%